Personnel administration in the federal government / Miriam Lewis - Lewis, Miriam (Estados Unidos de America: The Brookings Institution, 1937)
Elements of the personnel problem, the elimination of spoils, positive personnel administration, personnel work not separated from regular admnistration, funtionalized peronnel wowrk under management, relationship between general adminstrative officers and personnel officer; control personnel functions, promotional, educational personnel administration, divided control over the administrtive branch, criticisms of civil service commission examined, sins of omission, quasi juditial functions of civil service commission.
Contents
Col. Admón
Keywords: 1. FEDERAL SYSTEMS 2. PERSONNEL MANAGEMENT - FEDERAL GOVERNMENT 3. ADMINISTRATION